An. gambiae gSG6-P1 evaluation as a proxy for human-vector contact in the Americas: a pilot study. Issue 1 (December 2015) - Londono-Renteria, Berlin; Drame, Papa; Weitzel, Thomas; Rosas, Reinaldo; Gripping, Crystal; Cardenas, Jenny; Alvares, Marcela; Wesson, Dawn; Poinsignon, Anne; Remoue, Franck; Colpitts, Tonya
Abstract Background During blood meal, the female mosquito injects saliva able to elicit an immune response in the vertebrate. This immune response has been proven to reflect the intensity of exposure to mosquito bites and risk of infection for vector transmitted pathogens such as malaria. The peptide gSG6-P1 ofAn. gambiae saliva has been demonstrated to be antigenic and highly specific toAnopheles as a genus. However, the applicability of gSG6-P1 to measure exposure to differentAnopheles species endemic in the Americas has yet to be evaluated. The purpose of this pilot study was to test whether human participants living in American countries present antibodies able to recognize the gSG6-P1, and whether these antibodies are useful as a proxy for mosquito bite exposure and malaria risk. Methods We tested human serum samples from Colombia, Chile, and the United States for the presence of IgG antibodies against gSG6-P1 by ELISA. Antibody concentrations were expressed as delta optical density (ΔOD) of each sera tested in duplicates. The difference in the antibody concentrations between groups was tested using the nonparametric Mann Whitney test (independent groups) and the nonparametric Wilcoxon matched-pairs signed rank test (dependent groups). All differences were considered significant with aP < 0.05. Results We found that the concentration of gSG6-P1 antibodies was significantly correlated with malaria infection status and mosquito bite exposure history. People with clinical malaria presented significantly higher concentrations of IgG anti-gSG6-P1 antibodies than healthy controls. Additionally, a significant raise in antibody concentrations was observed in subjects returning from malaria endemic areas. Conclusion Our data shows that gSG6-P1 is a suitable candidate for the evaluation of exposure toAnopheles mosquito bites, risk of malaria transmission, and effectiveness of protection measures against mosquito bites in the Americas.